European Oncology Leaders The CancerFutures Collection 2001-2004. - SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
CancerFutures was launched in 2001 with the aim of increasing knowledge about the complex world of cancer care through people and facts. Cover Story and Masterpiece are two key sections of the magazine that have featured in-depth interviews with some of Europe’s most influential oncology leaders – people who have been pioneers of the art and science of oncology over the past 30 years. These interviews comprise a unique collection of stories that give insight into the many personal and professional challenges these leaders have faced in building their careers and pushing forward the boundaries of oncology practice. The European School of Oncology is pleased to launch the CancerFutures Collection which will be of interest to all members of the European oncology community, both today and in the future. This collection acknowledges the tremendous contribution that these leaders have made to cancer care and pays tribute to their dedication and drive. It will provide encouragement for all those confronted with difficulties in building their careers, and will give some inspiration for future leaders.
Cover Stories -- Martine Piccart: Medic and Musician… -- Gordon McVie: Making Waves -- Agnes Glaus: Softly Softly -- Mariano Barbacid: The Homecoming -- Liisa Elovainio: Tough on Tobacco -- Franco Cavalli: Rebel with (Several) Rauses -- Françoise Meunier: Chameleon Chief -- Jean-Pierre Armand: Sifting Sand -- Silvia Marsoni: The Go-Between -- Harry Bartelink: Putting Europe First -- Nora Kearney: Shaking Up the Big House -- Paris and Helen Kosmidis: A Legend in their Own Time -- Jacek Jassem: Reaching out From Gdansk -- Masterpieces -- Interview with Umberto Veronesi -- Maurice Tubiana: The Fighting Spirit Behind Cancerology -- Michael Baum: Shooting Sacred Cows -- Hans-Jörg Senn: Championing Consensus -- Gianni Bonnadona: Fighting for Every Life.
Keywords: Oncology .; Oncology